Temporal analysis of threats causing species endangerment in the United States. Issue 8 (17th June 2019) - Leu, Matthias; Haines, Aaron M.; Check, Courtney E.; Costante, Delaney M.; Evans, Jessica C.; Hollingsworth, Margaret A.; Ritrovato, Isabel T.; Rydberg, Ann Marie; Sandercock, Alexander M.; Thomas, Kayli L.; Treakle, Tyler C.
Abstract: Understanding temporal variation of threats that cause species endangerment is a key to understand conservation strategies needed to improve species recovery. We assessed temporal variation in the threats to species listed under the United States Endangered Species Act (ESA) as identified by the United States Fish and Wildlife Service (USFWS) and National Marine Fisheries Service (NMFS). Based on initial review of ESA listing decisions and literature, we identified six overarching threat categories: habitat modification, overutilization, pollution, species–species interaction, demographic stochasticity, and environmental stochasticity. We screened listing decision documents to determine threat occurrence (i.e., presence/absence of a given threat in a listing decision) for each threat category for all species listed between 1975 and 2017. We evaluated how the number of threats and specific threat occurrences changed over the past four decades. We found that the number of threats per listing decision increased more than twofold from an average of 1.5 (95% CI: 1.3–1.7) threats in 1975 to 3.7 (95% CI: 3.4–4.0) threats in 2017. Threat occurrence increased for habitat modification, environmental stochasticity and species–species interaction, while it decreased for overutilization since 1975 and for demographic stochasticity and pollution since the mid‐2000s. The documented increase in number of threats at time of listing may be due to a growing human population exerting increased pressure on species persistence, improved scientific advancement in understanding factors influencing species endangerment, or prolonged time taken for more recent species to be listed under the ESA. We believe that key federal and state governmental regulations have resulted in a documented decrease in overutilization, demographic stochasticity, and pollution, and we recommend large‐scale strategies combined with local planning efforts to address the growing threats of habitat loss, environmental stochasticity, and species–species interaction.